Economic benefits of methylmercury exposure control in Europe : monetary value of neurotoxicity prevention - Bellanger, Martine (2015)
© 2013 Bellanger et al.; licensee BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.